Structural reliability analysis in randomic excitation signs applying linear-experimental and bioengineering statistical methods (Research, Society and Development, 2020)
This work demonstrates a study of linear-experimental statistical methods and the negative selection artificial immune system, applied to the random excitation of a structural dynamic system. In the development of this work, a two-storey shear building structure was randomly excited, and the failure was caused by a random external disturbance, whose noisy signal was treated by the Wiener filter and subsequently applied the linear-experimental statistical method and artificial immune system. negative selection. The result of both applications allowed a targeted and objective analysis, demonstrating that the signal spectrum contains qualitative and quantitative levels of great significance in engineering applications.